Assessment of the Occurrence and Concentration of Heavy Metals in Spring Waters - Anyanwu, Emeka Donald; Adetunji, Onyinyechi Gladys (Modern Advances in Geography, Environment and Earth Sciences Vol. 4, 2021)
The aim of this study was to assess the occurrence and concentrations of heavy metals in spring waters and determine its suitability for human consumption. Eight (8) heavy metals (Mn, Cu, Pb, Fe, Zn, Cd, Cr and Ni) were recorded. Manganese, chromium, lead, iron and cadmium exceeded acceptable limits, which could be attributed to geogenic source exacerbated by seasonal and anthropogenic influences. The values of some of these metals were high and could pose serious health risk to the consumers of spring waters. Therefore, spring waters may not be suitable for drinking but can used for other domestic purposes.